Development of Poetry Writing Teaching Materials Using Gamification Media at SMA Negeri 81 East Jakarta - Yohana K Sihombing; Fathiaty Murtadho; Siti Ansoriyah (Journal of Educational Sciences, 2026)
This study aims to develop poetry writing teaching materials using gamification media through the Jumenly platform at SMA Negeri 81 East Jakarta. The research is based on real challenges faced by students in poetry writing, particularly in choosing appropriate diction, creating vivid imagery, and expressing ideas creatively. These difficulties lead to low motivation and interest in learning, emphasizing the need for innovative and technology-based teaching materials. To address this issue, the research adopts the ADDIE development model, which includes five systematic stages: Analysis, Design, Development, Implementation, and Evaluation. The study found that 98.7% of students demonstrated high interest in poetry learning but still required interactive and engaging media. The development of gamification-based teaching materials led to significant improvements in students’ poetry writing skills and creative thinking abilities. Expert validation confirmed that the materials were highly valid and suitable for classroom use. The implementation results showed a 35% increase in poetry writing skills and a 40% enhancement in creative thinking. Overall, this study contributes to innovative, technology-integrated learning that fosters creativity, engagement, and meaningful learning experiences in Indonesian language and literature education.